PERIPHERAL NEUROPATY AND CLINICAL SIGNS OF ACUTE CORONARY SYNDROME IN PATIENTS WITH DIABETES MELLITUS - Rita Simone Lopes Moreira; Solange Guizzilini; Vinicius Batista Santos (Universidade Federal do Paraná, 2017)
This study aimed to assess the severity of peripheral neuropathy in diabetic patients with acute coronary syndrome and its association with the severity of clinical signs. Prospective, cross-sectional and quantitative study. Data were collected from November 2015 to February 2016 in a hospital in the city of São Paulo. The clinical signs of diabetic patients with acute coronary syndrome were analyzed and the intensity of peripheral neuropathy was assessed using the Neuropathic Symptom Score (NSS). Fifty patients were assessed, and 33 (66%) participants had precordial catch syndrome, as well as sweating and dyspnea. Neuropathic symptoms were also identified in 33 (66%) patients, and there was no association between intensity of neuropathy and intensity of clinical signs of acute coronary syndrome. The clinical assessment of diabetic patients with acute coronary syndrome by nurses should be very careful, especially in patients with atypical clinical signs, depending onthe degree of peripheral neuropathy.